Effects of the Germinated Glycine max and Angelica gigas Nakai Mixture on Hepatic Lipid Metabolism and Bone Turnover Balance in Ovariectomized Rats - Sangmin Lee; Yunsang Cho; Jihye Choi; Hwal Choi; Tae Sung Jung; Jungkee Kwon (Applied Sciences, 2023)
Women going through menopause experience changes in their hormone levels, such as decreased estrogen secretion. Those changes can lead to weight gain and steatosis (fatty liver) due to abnormal lipid metabolism and bone turnover. Natural herbal medicines have been developed to treat and prevent menopausal symptoms. The aim of this study was to evaluate how a mixture of germinated Glycine max (GG) and Angelica gigas Nakai (AG) affected serum lipid profile levels, hepatic damage, inflammation, and bone turnover in ovariectomized (OVX) rats. The animals were randomly allocated into six groups: Sham control group (Sham), OVX control group (OVX), OVX + 50 mg/kg b.w. of GG (GG50) group, and OVX + 25, 50, 100 mg/kg b.w. of GG and AG mixture (GAM; GAM25, GAM50, GAM100) groups. After four weeks of treatment, the GAM groups exhibited decreases in serum lipid profile levels (TC, TG, and Low Density Lipoprotein (LDL)) and increases in High Density Lipoprotein (HDL). Proinflammatory mediators (IL-1β, IL-6, TNF-α, and iNOS) were reduced after the administration of GAM, and the degree of liver damage (ALT, AST) also decreased. Bone resorption (CTX1, NTX1, osteoclasts in H&E staining) decreased in the GAM-treated groups, and bone morphometric markers (BMD, BV/TV, Tb.N) improved compared with the OVX group. Additionally, increased bone formation (ALP, mineralization) and decreased bone resorption (TRACP) were confirmed in in vitro experiments. These results suggest that GAM has anti-obesity and anti-inflammatory effects by preventing dyslipidemia and that it alleviates bone mass loss in OVX rats by inhibiting osteoclastogenesis.